FAMILY SOCIAL SUPPORT FOR THE ELDERLY IN SUGIHWARAS VILLAGE, PRAMBON DISTRICT, NGANJUK REGENCY - Adiwidya Wicaksono, Hanasta; Susilowati, Ellya; Pradytia, Wendy; Rosilawati (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study examines the forms and intensity of family social support provided to elderly individuals in Sugihwaras Village, Prambon Subdistrict, Nganjuk Regency, through four key dimensions: emotional, esteem, instrumental, and informational support. In the context of rural communities, where institutional services are often limited, the family functions as the primary support system in ensuring the physical and psychosocial well-being of elderly individuals. Utilizing a descriptive quantitative research design, the study employed a census method involving 37 elderly individuals cohabiting with family members. Data were collected through structured questionnaires and document analysis. The results indicate that the overall level of family social support is high. Among the four dimensions, instrumental support scored the highest, reflecting substantial family engagement in fulfilling daily physical needs. In contrast, esteem support recorded the lowest score, highlighting a lack of symbolic acknowledgment and emotional affirmation. These findings emphasize the need for comprehensive strategies that strengthen not only functional caregiving but also the affective and symbolic aspects of support, in order to foster dignity, autonomy, and meaningful aging.